Efektifitas Biji Kelor (Moringa oleifera Lamk) Sebagai Koagulan Besi (Fe) Dan Kalsium (Ca) - Akbar, Akbar; Said, Irwan; Diah, Anang Wahid M. (Universitas Tadulako, 2015)
Research about coagulation of iron and calcium have been conducted using moringa (moringa oleifera Lamk) seed coagulant through the variation of the concentration of moringa seed and depositional time. Moringa seeds were used in this research that moringa seeds are old and dry. Compounds of moringa seeds that play role in the coagulation process of iron and calcium are proteins. This research was conducted to determine the optimum concentration of moringa seed and optimum deposition time on the process of coagulation using moringa seed coagulant in order to obtain the percentage decrease in the levels of iron and calcium. Variations in the concentration of moringa seeds were used in this research are 100, 200, 300, 400 and 500 ppm and the settling time is 30, 60, 90, 120 and 150 minutes. The results showed that the concentration of moringa seed and deposition time influenced in the process of coagulation of iron and calcium. In iron coagulation, obtained optimum concentration of 400 ppm moringa seeds and optimum settling time is 90 minutes. In these conditions the iron content decreased by 68.00 ppm or 66.95% from its initial level of 99.8 ppm. While the calcium coagulation, moringa seeds obtained optimum concentration of 500 ppm and optimum settling time of 120 minutes, which in this condition calcium levels decreased by 241 ppm or 49.00% of the initial concentration is 492 ppm.